2022
DOI: 10.3390/machines10040245
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Reweighted Domain Adaption for Cross-Domain Bearing Fault Diagnosis

Abstract: Certain progress has been made in fault diagnosis under cross-domain scenarios recently. Most researchers have paid almost all their attention to promoting domain adaptation in a common space. However, several challenges that will cause negative transfer have been ignored. In this paper, a reweighting method is proposed to overcome this difficulty from two aspects. First, extracted features differ greatly from one another in promoting positive transfer, and measuring the difference is important. Measured by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…However, these data still conform to the same machine health condition, and there are common basic characteristics among them. Therefore, it is feasible and promising to study the knowledge transfer of fault diagnosis among different sensors [ 210 , 211 , 212 ]. The fourth is different machines; Guo et al [ 213 ] combined adversarial discriminant methods and difference-based methods, using MMD to narrow the differences between features after acquiring domain-independent features in the shared space through adversarial training, which is one of the earliest jobs of different machines.…”
Section: Challenges and Prospects Of Dtl In Industrial Fault Diagnosismentioning
confidence: 99%
“…However, these data still conform to the same machine health condition, and there are common basic characteristics among them. Therefore, it is feasible and promising to study the knowledge transfer of fault diagnosis among different sensors [ 210 , 211 , 212 ]. The fourth is different machines; Guo et al [ 213 ] combined adversarial discriminant methods and difference-based methods, using MMD to narrow the differences between features after acquiring domain-independent features in the shared space through adversarial training, which is one of the earliest jobs of different machines.…”
Section: Challenges and Prospects Of Dtl In Industrial Fault Diagnosismentioning
confidence: 99%
“…Traditional machine learning algorithms perform poorly when the training and test data come from different distributions. In this case, domain adaptation becomes useful [36]. A domain consists of a data space, x, and a probability distribution, P X , on its samples X ∈ x. Domain adaptation means to adapt useful knowledge from a source domain, S, to a target domain, T. Specifically, we are provided a source dataset (X S ,…”
Section: Domain Adaptationmentioning
confidence: 99%
“…Zhang et al demonstrated the use of cross-domain adversarial learning for machine fault diagnosis using training and testing data collected under different operating conditions [16]. Interestingly, Meng et al [17] computed a balance factor between domain adaptation and class discrimination during bearing fault diagnosis in machines. They chose a dynamic weighted strategy to reduce instances of negative transfer during domain adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our proposed approach also addresses sample selection bias in intermittent error-prone data arising from sensor quality and noise. Lin et al [12] and Meng et al's [17] approaches are strong motivators for the use of cross-domain learning in our machine status monitoring work. However, using CNNs and transfer learning and the associated need for complex computing resources makes their approach somewhat complex for use with lowcost and often constrained edge processing systems.…”
Section: Introductionmentioning
confidence: 99%